INTEGRATION OF ISLAMIC EDUCATION AND MODERN SCIENCE: BUILDING COLLABORATION WITHIN THE ISLAMIC SCIENTIFIC PARADIGM - Harahap, Nazua Fatia; Azwa, Nurul; Fitriyanti, Yuli; Sari, Herlini Puspika (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
The integration of Islamic education and modern science is crucial to overcoming the long-standing dichotomy that positions religious and empirical knowledge as opposing domains. This study aims to examine the conceptual foundation and practical opportunities for building a collaborative scientific paradigm that unites Islamic spiritual values with modern scientific rationality. Using a qualitative descriptive design, this research relies on library studies and content analysis of scholarly works related to Islamic epistemology, the Islamization of knowledge, and integrated education models. The findings show that the dichotomy between Islamic education and modern science stems from epistemological misconceptions influenced by secular educational systems, which separate divine revelation from rational inquiry. Islamic epistemology views all knowledge as originating from Allah and therefore positions religious and scientific disciplines as inherently interconnected. The study identifies three key areas of integration: curriculum development grounded in tawhid, reflective and interdisciplinary learning strategies, and strengthening the role of teachers as murabbi who bridge spiritual and scientific dimensions. This integrative paradigm enables the formation of ulul albab individuals—those who are intellectually critical, spiritually grounded, and ethically responsible in their use of knowledge. Consequently, Islamic education and modern science should be perceived not as competing entities but as complementary pillars that collectively contribute to building a holistic, civilized, and God-centered educational system.